2015
DOI: 10.1089/chi.2014.0071
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Mediates the Effects of Low Income on Preschool Children's Executive Control, with Implications for Behavior and Academics

Abstract: Background: Children from low-income backgrounds are more likely to have cognitive impairments, academic problems, and obesity. Biological mechanisms for the relationship between adiposity and neurocognitive functioning have been suggested, but the direction of effects is unclear.Methods: The relations among income, BMI, and cognitive-behavioral functioning were modeled longitudinally. Children (n = 306) were assessed at 36-39 months (Time 1; T1) and 63-67 months (Time 4; T4) through anthropometry, measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Following Cipriano and Stifter's () procedures, we created a composite EC score by weighting each scale according to its total number of items and then summing the three products together. Composite scores are recommended and commonly used (Allan & Lonigan, ; Belfort et al ., ; Sulik, Blair, Mills‐Koonce, & Greenberg, ; Tandon, Thompson, Moran, & Lengua, ), as they increase scale reliability, reduce random error, and provide parsimony (Holmes et al ., ; Rushton, Brainerd, & Pressley, ). Higher scores indicated stronger EC, α = .83.…”
Section: Methodsmentioning
confidence: 99%
“…Following Cipriano and Stifter's () procedures, we created a composite EC score by weighting each scale according to its total number of items and then summing the three products together. Composite scores are recommended and commonly used (Allan & Lonigan, ; Belfort et al ., ; Sulik, Blair, Mills‐Koonce, & Greenberg, ; Tandon, Thompson, Moran, & Lengua, ), as they increase scale reliability, reduce random error, and provide parsimony (Holmes et al ., ; Rushton, Brainerd, & Pressley, ). Higher scores indicated stronger EC, α = .83.…”
Section: Methodsmentioning
confidence: 99%
“…44,74,75 Poor EF may contribute to obesity risk by reducing self-regulation capacity, but the association could be bidirectional. 44,55,74 Experimental studies in adults have shown that EF skills, particularly working memory, can improve after dietary changes 76 and surgically-induced weight loss.…”
Section: Mechanisms Of Ef – Pediatric Obesity Association Are Poorly mentioning
confidence: 99%
“…In support, a relationship between early changes in feeding and HPA-axis functioning has been demonstrated in humans 9 . Regarding cognition, there is consistent evidence linking maternal obesity, which can influence neonatal nutrition, with lower cognitive function in children 10 , such as lower performance in pattern construction 11 , lower executive control functions 12 , 13 , and reduced action monitoring 14 . These cognitive impairments can have negative implications for daily life functioning and express a need for intervention.…”
Section: Introductionmentioning
confidence: 99%